Analisis Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Untuk Berkarir Menjadi Akuntan Publik(Studi kasus pada Mahasiswa Akuntansi Universitas Muhammadiyah Surakarta) - Dwisantoso, Arif; , Drs. Agus Endro Suwarno, Ak., M.Si (2017)
This study aims to provide empirical evidence of the effect: the analysis of the factors that affect student interest in accounting careers become public accountant (a case study on accounting students Muhammadiyah University of Surakarta). The method of collecting samples by using purposive sampling technique. This study was conducted using data Primary. The population in this study were 60 students of Muhammadiyah University of Surakarta accounting. The analytical method used is multiple regression analysis. The results of this study prove that the variables professional recognition, social values, environmental violence personalities affect the interests of students, while variable financial award and labor market considerations do not affect the interest of accounting students into public accounting career.